2013
DOI: 10.1182/blood-2012-06-440354
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Sirpa is the genetic determinant for NOD-based mouse lines to achieve efficient human cell engraftment

Abstract: Key Points• NOD-specific Sirpa polymorphism is the genetic determinant of highly efficient xenograft activity in NOD-based immunodeficient mouse models.Current mouse lines efficient for human cell xenotransplantation are backcrossed into NOD mice to introduce its multiple immunodeficient phenotypes. Our positional genetic study has located the NOD-specific polymorphic Sirpa as a molecule responsible for its high xenograft efficiency: it recognizes human CD47 and the resultant signaling may cause NOD macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 47 publications
3
87
0
Order By: Relevance
“…18,19 Various methods have been used to surmount the problem of mouse SIRPa-human CD47 incompatibility to produce humanized mice in non-NOD strains. Legrand et al 20 showed that transgenic expression of mouse CD47 on human HSC facilitated engraftment in a BALB/c Rag2 17 successfully surmounted this obstacle in a HIS model using DKO mice expressing a NOD SIRPa transgene. These studies indicate that the lack of tolerization of the phagocytic compartment in C57BL/6 mice is an important barrier to successful humanization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Various methods have been used to surmount the problem of mouse SIRPa-human CD47 incompatibility to produce humanized mice in non-NOD strains. Legrand et al 20 showed that transgenic expression of mouse CD47 on human HSC facilitated engraftment in a BALB/c Rag2 17 successfully surmounted this obstacle in a HIS model using DKO mice expressing a NOD SIRPa transgene. These studies indicate that the lack of tolerization of the phagocytic compartment in C57BL/6 mice is an important barrier to successful humanization.…”
Section: Introductionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From C57BL/6 mice express a form of the signal recognition protein a (SIRPa) receptor that does not recognize human CD47. 16,17 SIRPa-CD47 recognition transmits antiphagocytic signals necessary to prevent engulfment and clearance of transplanted human cells by macrophages. 18,19 Various methods have been used to surmount the problem of mouse SIRPa-human CD47 incompatibility to produce humanized mice in non-NOD strains.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SIRPa was shown to express different alleles in both human and mice populations (11). Consistent with this function, the ability of NOD immune-deficient hosts to promote immune reconstitution upon hHSC engraftment was attributed to better xenogeneic hCD47/mouse SIRPa recognition, leading to the inhibition of human donor cell destruction by murine phagocytes both in vitro and in vivo (11,29).…”
Section: Discussionmentioning
confidence: 84%
“…CD47 binds to sirpa to send a signal inhibiting phagocytosis by self-macrophages. Although mouse macrophages basically eliminate xenogeneic cells due to inability of xenogeneic CD47 to bind to mouse sirpa, human CD47 can bind to sirpa encoded by the NOD-derived allele to avoid elimination of human cells by the NOD background macrophages (5,6). Resembling hepatic metastases of HCT116 cells transferred to NOG hosts in the present study, reconstitution of human platelets and erythrocytes in the periphery was suppressed by host macrophages in contrast to that of leukocytes in the periphery and of all lineages of hematopoietic cells in the marrow in NOG hosts in previous studies (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…IL-2Rg c signaling is required for development of NK cells and a subset of dendritic cells (DCs) producing IFN-g represented by the CD11c + B220 + CD122 + phenotype (3,4). The allele of Sirpa gene in the NOD background mice allows human CD47 to bind to the encoded signal regulatory protein a (sirpa) to inhibit macrophage phagocytosis of human cells (5,6). The details of how such alteration in innate immunity contributes to the engraftment are of considerable interest but still remain to be elucidated.…”
mentioning
confidence: 99%